MANAJEMEN ASUHAN KEBIDANAN INTRANATAL PADA NY “D” DENGAN ANEMIA DI RSIA SITTI KHADIJAH I MUHAMMADIYAH MAKASSAR - Fatmah Junia Sari Bahasoan; Zelna Yuni Andryani; Syatirah (Jurnal Midwifery, 2022)
Introduction Anemia is a decrease in the haemoglobin. Mild anemia Hb <10 gr/dl, moderate anemia Hb 7-8 gr/dl, and severe anemia Hb <6 gr/dl. WHO announced that anemia was considered to be the major cause of maternal mortality during pregnancy and childbirth delivery The findings of previous research showed that the presentage of maternal mortalitiy during childbirth because of anemia was 70%, while the were only about 19.7% of cases due to other reasons. Therefore, based on the aforementioned problem, it is essential to conduct proper treatment in dealing with high occurrences of anemia in childbirth. The purpose of this study was to investigate and provide internal midwifery care management on a pregnant patient with anemia at RSIA Sitti Khadijah I of Muhammadiyah Makassar. Method The Research was conducted in accordance with health and midwifery standars by using the 7-stages of varney midwifery care management and SOAP documentation procedure. Result The findings of this study indicated that despite the anemia problem faced by Mrs. “D” the delivery from the stage I to IV was considered to be running well and normal without any complications. Moreover, the newborn was also in good and healthy condition. This study concluded that the treatment of the patient was well conducted where the anamnesis and regular monitoring. Conclusion Furthermore, the assessment, analysis, and documentation related to all actions and treatment were documented. Hence, it could be suggested that the findings of this research were in line with previous theories.